Lapbook interaktif: Media alternatif yang efektif dan terjangkau untuk meningkatkan pemahaman belajar siswa - Budianto, Putri; najach, M Miftachun; Radif Ali, Abd Adiem (Maliki Interdisciplinary Journal, 2025)
Islamic Cultural History lessons are often considered boring because there is too much memorization and minimal interesting activities. To overcome this, this study developed a learning media in the form of a lapbook using the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Literature review shows that media that involve visual and physical activities can increase students’ interest and understanding. Lapbooks that were made in groups and then tested on friends from other classes showed positive results. Most respondents stated that lapbooks were interesting and helped them understand the material more easily. With lapbooks, students will become more active, confident, and enthusiastic about learning because they are directly involved in making learning media. Lapbooks are also flexible, easy for teachers to use, and suitable for schools with limited technology. These results show that simple media such as lapbooks can have a big impact on creating more enjoyable, interactive, and meaningful history learning.